Profile of HIV subtypes in HIV/HBV- and HIV/HCV-coinfected patients in Southern Brazil - Avanzi,Valéria Miranda (2017)
Abstract INTRODUCTION: HIV and viral hepatitis infections are major causes of chronic disease worldwide and have some similarities with regard to routes of transmission, epidemiology, front barriers faced during access of treatment, and strategies for a global public health response. The objective was to describe the HIV-1 subtypes, viral tropism and single-nucleotide polymorphisms (SNPs) of interleukin 28B (IL28B) from a case series of HIV/viral hepatitis coinfected patients from southern Brazil. METHODS: Clinical and epidemiological data were evaluated by a review of medical records. Periodic blood draws were taken to determine the viral and host characteristics. RESULTS: This study included 38 patients with HIV/HBV or HIV/HCV coinfection; the median age was 49 years. Thirty-seven (97.4%) were on antiretroviral therapy, 32 (84.2%) had an undetectable viral load, a median CD4+ T-cell count of 452 cells/mm3. HIV-1 subtyping showed 47.4 and 31.6% of patients with subtypes C and B, respectively. Analysis of viral co-receptor usage showed a predominance of the R5 variant (64.7%), with no significant difference between the subtypes. Twenty patients with HIV/HCV coinfection were eligible to receive HCV therapy with pegylated-interferon-alpha plus ribavirin, and 10/20 (50%) of them achieved sustained virological response. SNPs of IL28B were evaluated in 93.3% of patients with HIV/HCV coinfection, and 17 (60.7%) presented the CC genotype. CONCLUSIONS: In the present case series, a higher frequency of HIV subtype C was found in coinfected patients. However such findings need to be prospectively evaluated with the inclusion of data from regional multicenter analyses.